Stress Management among Nurses managing burns patients in National Orthopaedic Hospital, Enugu - Mbia, Pamela; Iwara, Catherine; James, Runyi (Transdisciplinary Journal of Education & Sustainable Development Studies, 2026)
This study was carried out to assess stress management among nurses managing burns patients in National Orthopaedic hospital Enugu. The research was guided by the three research questions and the objectives which aimed at identifying the stressful situations among nurses and factors contributing to nurse stress and procedures used in managing stress. Related literatures were reviewed and descriptive research design was used for this study. The total population of the 82 burns and plastic nurses were used for the study. A self-structured questionnaire with close ended questions to collect data for this study was used. Data gotten was analyzed using the statistical package of social science (SPSS) version 24 into frequency and simple percentage. The findings revealed that (3.6%) observed that standing for long hours dressing burns patient. (3.5%) had high job demand which ranked the highest (2.5%) indicated that break, casual or annual leave can help and reduce the stressful situation in NOHE. Based on the findings, recommendations were made which include, the need to give incentives to nurses managing burns patient, hospital management should support nurses who are interested in Burns and Plastic training in order to reduce job demand in NOHE. Encouragement of work shape for nurses, and employment of more nurses in other to reduce the work load on burns and plastic nurses.